An inner filter effect based sensing system for the determination of caffeine in beverage samples. Issue 6 (30th January 2020) - González, Natalia; Lantmann Corral, Sara P.; Zanini, Graciela; Montejano, Hernán; Acebal, Carolina C.
Abstract : A chemosensing system for the determination of caffeine in beverage samples using glibenclamide as a fluorophore. Abstract : In this work, the inner filter effect (IFE) of caffeine (CF) over the fluorescence signal of glibenclamide (GLB) was used for the determination of CF in beverage samples. The system worked in a turn-off mode since the absorption spectrum of CF overlaps the excitation band of GLB resulting in a decline in its fluorescence signal ( λ exc = 234 nm, λ em = 350 nm). No changes in the fluorescence lifetime of GLB (0.29 ns) were observed in the presence of CF up to 127.6 mg L −1 concentration. The parameters that affect the fluorescence intensity were investigated, such as fluorophore concentration (16 mg L −1 ), pH (3.2) and temperature (25 °C). Under optimized conditions, the IFE-based approach can determine CF in a range between 1.00 and 100.0 mg L −1, with a detection limit (LOD) of 0.10 mg L −1 . The relative standard deviation (% RSD) values for the intra-day and inter-day precision were 0.75 and 1.24, respectively. The new method was successfully tested in the determination of the target analyte in beverage samples without previous treatment. The results were compared with those obtained by a reference method, leading to the conclusion that there were no significant differences at the studied confidence level ( α = 0.05).